1989
DOI: 10.1111/j.1365-2915.1989.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of outer caudal setae on all larval instars of Phlebotomus tobbi from the Ionian Greek islands

Abstract: Larval instars 2, 3 and 4 of Phlebotomus tobbi Adler, Theodor & Lourie from the Greek islands of Corfu and Zakynthos were found to have two caudal setae instead of the four usually present on these instars of Phlebotomus larvae. In a scanning electron microscope comparison with larvae of P. papatasi (Scopoli), a sensillum was seen in place of each outer seta of P. tobbi larvae, suggesting secondary loss of the setae. As the larvae of less than a tenth of the species and subspecies of the genus Phlebotomus have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…According to Killick-Kendrick et al (1989) the function of these setae is obscure. The distinctive backand forth movement of the long setae of larvae and their fine hair suggest the presence of sensillae.…”
Section: Discussionmentioning
confidence: 99%
“…According to Killick-Kendrick et al (1989) the function of these setae is obscure. The distinctive backand forth movement of the long setae of larvae and their fine hair suggest the presence of sensillae.…”
Section: Discussionmentioning
confidence: 99%
“…According to Killick-Kendrick et al (1989) the function of these setae is obscure, although they observed a basal sensilla on the probable points of one of the naturally absent pairs of caudal setae of P. tobbi. The distinctive back-andforth movement of the long setae of larvae of L. whitmani and L. intermedia led Barretto (1940), to suggest the presence of sensillae.…”
Section: Discussionmentioning
confidence: 99%
“…Up to that time, all descriptions and morphological observations were made by light microscopy. Studies of sand fly larvae with scanning electronic microscopy (SEM) were initiated by Killick-Kendrick et al (1989) on Old World species Phlebotomus tobbi. In South America, Willians (1996, 1997) described by SEM the larvae of fourth and first instar of L. longipalpis.…”
mentioning
confidence: 99%
“…Although the characteristics of insect pre‐imaginal stages are as important in taxonomy as those of adults ( van Emden 1957), the larvae of most sandfly species have never been described or observed and few morphological characteristics of taxonomic importance have been identified ( Killick‐Kendrick et al . 1989 ).…”
Section: Discussionmentioning
confidence: 99%